Marketing Mix Effect on Purchase Decision of Traditional Jamu Sabdo Palon - Risa Afida Nuraini; Heny Kurnianingsih (Institute of Computer Science (IOCS), 2021)
The current Covid-19 pandemic has made herbal medicine producers experience an increase because herbal medicine is an alternative in boosting immunity. The purpose of this study was to determine the effect of the marketing mix (product, location, promotion, price, process, employees and physical evidence) the decision to buy the traditional herbal medicine Sabdo Palon. This study used a sample of 80 respondents using purposive sampling technique. The data analysis technique used instrument test, classical assumption test and multiple linear regression analysis. Simultaneously, product, place/location, promotion, price, process, people/employee and physical evidence variables have a significant influence on purchasing decisions but partially purchasing decisions are not influenced by product, location, promotion, price, process, employee and physical evidence variables.